METTL3 Attenuates LPS-Induced Inflammatory Response in Macrophages via NF-κB Signaling Pathway - Jinghua Wang; Shushan Yan; Hongying Lu; Shufeng Wang; Donghua Xu (Mediators of Inflammation)
Methyltransferase-like 3 (METTL3), an RNA N6-methyladenosine (m6A) methyltransferase, is essential for the m6A mRNA modification. As a key enzyme of m6A methylation modification, METTL3 has been implicated in immune and inflammation regulation. However, little is known of the role and underlying mechanism of METTL3 in rheumatoid arthritis (RA). The aim of the present study is to elucidate the function and potential mechanism of METTL3 in RA pathogenesis. We used quantitative real-time polymerase chain reaction to detect the expression of METTL3 in RA patients and controls as well as the macrophage cell line. CCK-8 was used for cell proliferation assay. Enzyme-linked immunosorbent assay (ELISA) was adopted to estimate the generation of IL-6 and TNF-α in macrophages. Western blot and immunofluorescence were applied to evaluate the activation of NF-κB in macrophages. The expression of METTL3 was significantly elevated in patients with RA. It was positively associated with CRP and ESR, two common markers for RA disease activity. Besides, LPS could enhance the expression and biological activity of METTL3 in macrophages, while overexpression of METTL3 significantly attenuated the inflammatory response induced by LPS in macrophages. Moreover, the effect of METTL3 on LPS-induced inflammation in macrophages was dependent on NF-κB. This study firstly demonstrates the critical role of METTL3 in RA, which provides novel insights into recognizing the pathogenesis of RA and a promising biomarker for RA.